The influence of the business cycle on bankruptcy probability - Suzan Hol (Statistics Norway, Research Department, 2006)
I combine two fields of research on default prediction by empirically testing a bankruptcy prediction function where unlisted firms are evaluated on the basis of both their financial statement analysis and the macroeconomic environment. This combination is found to improve the default prediction compared to financial statements alone. The GDP-gap, a production index and the money supply M1 in combination with some financial health indicators for individual firms are found to be significant predictors on default for Norwegian firms during both a recovery and expansion in the 1990's.
Keywords: G32; G33; 330; bankruptcy prediction; macroeconomic environment; financial ratios; logit model